Kebijakan Integral Hukum Pidana dengan Technology Prevention dalam Upaya Pencegahan Kejahatan Cyberbullying - Firda Laily Mufid (Fakultas Hukum Universitas Islam Jember, 2018)
Cybercrime is human activity in the world mayantara who has made the computer as the evil deeds for example illegal access, to the destruction of the site , the interception of illegal , and the activities of humans which uses computers as the evil of the target credit card forgery for example, pornography via the internet. One of evil in the world mayantara namely cyberbullying that is a form of intimidation the guilty person or more to pigeonhole, discredit, to men through cyberspace. This intimidation do not haphazardly as a result, it was not uncommon death be the end of cyberbullying. Cyberbullying too are defined as a form of intimidation to which the offender do to harass his victims through technology device. Investors want to see someone gets hurt , there are a lot of the way they do to strike the victim with a message cruel and pictures of a disturbing and disseminated in order to embarrass incense to anyone Keywords: Cybercrime, cyberbullying, intimidation, technology